Genetic variability and population structure of endangered Panax ginseng in the Russian Primorye - Muzarok Tamara I; Kats Irina L; Reunova Galina D; Zhuravlev Yuri N; Bondar Alexander A (BMC, 2010)
Abstract Background The natural habitat of wild P. ginseng is currently found only in the Russian Primorye and the populations are extremely exhausted and require restoration. Analysis of the genetic diversity and population structure of an endangered species is a prerequisite for conservation. The present study aims to investigate the patterns and levels of genetic polymorphism and population structures of wild P. ginseng with the AFLP method to (1) estimate the level of genetic diversity in the P. ginseng populations in the Russian Primorsky Krai, (2) calculate the distribution of variability within a population and among populations and (3) examine the genetic relationship between the populations. Methods Genetic variability and population structure of ten P. ginseng populations were investigated with Amplified Fragment Length Polymorphism (AFLP) markers. The genetic relationships among P. ginseng plants and populations were delineated. Results The mean genetic variability within populations was high. The mean level of polymorphisms was 55.68% at the population level and 99.65% at the species level. The Shannon's index ranged between 0.1602 and 0.3222 with an average of 0.2626 at the population level and 0.3967 at the species level. The analysis of molecular variances (AMOVA) showed a significant population structure in P. ginseng. The partition of genetic diversity with AMOVA suggested that the majority of the genetic variation (64.5%) was within populations of P. ginseng. The inter-population variability was approximately 36% of the total variability. The genetic relationships among P. ginseng plants and populations were reconstructed by Minimum Spanning tree (MS-tree) on the basis of Euclidean distances with ARLEQUIN and NTSYS, respectively. The MS-trees suggest that the southern Uss, Part and Nad populations may have promoted P. ginseng distribution throughout the Russian Primorye. Conclusion The P. ginseng populations in the Russian Primorye are significant in genetic diversity. The high variability demonstrates that the current genetic resources of P. ginseng populations have not been exposed to depletion.